2012
DOI: 10.1093/infdis/jis577
|View full text |Cite
|
Sign up to set email alerts
|

Virological Surveillance of Influenza-Like Illness Among Children in Ghana, 2008–2010

Abstract: During the 3 years of influenza surveillance in Ghana, children aged <11 years bore a high burden of influenza-associated ILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
6
28
0
Order By: Relevance
“…Similarly, we found that 15.1% of ILI and 6.6% of SARI patients enrolled in our study tested positive for influenza A or B viruses over the 2 years period . For ILI cases, the prevalence of influenza increased with age, similarly to other studies . Particularly in very young children, the broad definition of “influenza‐like illness” leads to the inclusion of patients with respiratory infections caused by other pathogens, especially respiratory syncytial virus and rhinoviruses .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, we found that 15.1% of ILI and 6.6% of SARI patients enrolled in our study tested positive for influenza A or B viruses over the 2 years period . For ILI cases, the prevalence of influenza increased with age, similarly to other studies . Particularly in very young children, the broad definition of “influenza‐like illness” leads to the inclusion of patients with respiratory infections caused by other pathogens, especially respiratory syncytial virus and rhinoviruses .…”
Section: Discussionsupporting
confidence: 69%
“…Also successive waves of influenza circulation in 2014‐2015 were due to viruses from different subtypes and clades, as revealed by phylogenetic analyses of 14 A(H1N1)pdm09 and 29 A(H3N2) strains, suggesting new seeding events at least twice a year and sometimes within short time intervals (Figure ). Despite a possible lack of sensitivity due to non‐homogenous surveillance efforts, influenza viruses do not seem to circulate year‐round at background levels in Burkina Faso, similarly to Niger (analysis of FluNet data for Niger ‐ not shown ‐ and data from Mainassara et al) and unlike Côte d'Ivoire, Ghana or Togo, with a different climate. In the future, increased efforts toward sampling and individual strain characterization will help to better understand the temporal occurrence of influenza activity, virus spread between countries and potential persistence within West Africa …”
Section: Discussionmentioning
confidence: 99%
“…The obvious peaks in 2006 and 2009 were associated with a large epidemic or an outbreak of influenza, similar to the large-scale epidemic peak observed with the Victoria-like virus of influenza B that caused a flu outbreak at 12 schools in Ningbo from March to April 2006 [20]. The autumn peak in 2009 was largely influenced by the novel influenza A pH1N1 (pH1N1) activity, indicating the emergence of novel influenza viruses with pandemic potential [21], similar to the increased influenza activity during the pandemic period in Beijing, China [22]. After the pandemic period in 2009, the influenza epidemic intensity decreased in the following year because the population had acquired some level of protective antibodies after the pH1N1 infection.…”
Section: Discussionmentioning
confidence: 82%
“…Cough was one of the commonest symptoms reported. The reported cough could be pathological or non-pathological (Bonney et al, 2012). Though it is likely that a proportion of the symptoms reported may not be pathological, the prevalence of runny nose suggests a high probability of an upper respiratory tract infection (URTI).…”
Section: Discussionmentioning
confidence: 99%